2018
DOI: 10.1111/jcpt.12791
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between antimicrobial consumption and the prevalence of carbapenem-resistant Escherichia coli and carbapenem-resistant Klebsiella pneumoniae at a university hospital in Thailand

Abstract: Summary What is Known and Objective Carbapenem‐resistant Enterobacteriaceae (CRE) are virulent gram‐negative bacilli and cause urgent healthcare problems worldwide. One of the main factors leading to the emergence of CRE is antimicrobial consumption. The objective of this study was to assess how closely the rate of antimicrobial consumption and the prevalences of carbapenem‐resistant Escherichia coli (CR‐EC) and carbapenem‐resistant Klebsiella pneumoniae (CR‐KP) are correlated. Methods A retrospective study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“…However, there was no relevant research, and further studies were necessary to explore the mechanism. We also found that increasing the use of carbapenem or quinolones did not lead to a signi cant increase in the resistance of carbapenem among Enterobacteriaceae which was similar to a few previous studies [34][35][36]. But some studies showed that carbapenem or uoroquinolone use had a positive relationship with the incidence of CRE [35,37].…”
Section: Discussionsupporting
confidence: 89%
“…However, there was no relevant research, and further studies were necessary to explore the mechanism. We also found that increasing the use of carbapenem or quinolones did not lead to a signi cant increase in the resistance of carbapenem among Enterobacteriaceae which was similar to a few previous studies [34][35][36]. But some studies showed that carbapenem or uoroquinolone use had a positive relationship with the incidence of CRE [35,37].…”
Section: Discussionsupporting
confidence: 89%
“…One possible reason is that the successful spread of this RT was mainly due to its resistance to fluoroquinolones which provided an advantage over other less resistant RTs (38). Although there is high consumption of fluoroquinolones, such as levofloxacin, in the country (39), Thailand already harbours C. difficile RT 017, another epidemic RT with a high prevalence of resistance to fluoroquinolones, as well as other antimicrobials (14). Thus, it may have been difficult for C. difficile RT 027 to compete with this local RT compared to other regions.…”
Section: Discussionmentioning
confidence: 99%
“…From the 49 medium-scale farms (MSF), 94 isolates were from Ps, 44 isolates from Cs, and 24 isolates were from NCs. Several studies in farms in South-East Asia have looked at E. coli isolates from different livestock and farm workers (Nguyen et al, 2016;Lugsomya et al, 2018;Prakobsrikul et al, 2019); to build upon these studies we wanted to additionally assess farm production size in relation to P, C, and NC and look for differences between the six groups. To record significant differences between the isolate groups we used AST and WGS with in silico methods (Figure 1) to explore the genomic diversity (Read and Massey, 2014;Abdelgader et al, 2018;Boehmer et al, 2018).…”
Section: Selection Criteria Of Bacterial Isolates For Phenotypic and Genomic Analysismentioning
confidence: 99%
“…In locations where there is high AMU, there is also a high AMR burden (O'neill, 2016). This is of critical concern with antibiotic drugs, such as colistin, that are used as a last-resort drugs in humans to treat extensively resistant bacterial infections, e.g., carbapenem resistant Enterobacteriaceae (Wangchinda et al, 2018;Prakobsrikul et al, 2019) where very limited treatment options are available. Where last-resort drugs, such as colistin, are frequently used in livestock and in clinical settings generalized AMR can occur making these crucial drugs void and some bacterial infections untreatable (McEwen and Collignon, 2018).…”
Section: Introductionmentioning
confidence: 99%